Black-white mental status trajectories: What ages do differences emerge?. (December 2018) - Byrd, DeAnnah R.; Gee, Gilbert C.; Tarraf, Wassim
Abstract: Objectives: Studies of older U.S. adults have consistently found that African Americans perform worse on cognitive measures than whites, but there are inconsistencies as to whether these findings hold over time. Moreover, studies have focused on adults 51 and older, without considering younger ages; thus it is unclear the age at which these disparities surface. The present study examines black-white disparities in mental status trajectories among adults as young as 25 years over a 25-year period. Method: Data come from the Americans' Changing Lives Study (ACL) (n = 3, 617). Participants, ranging from ages 25–100 years old at baseline, were followed from 1986 to 2011 over 5 waves. Mental status was assessed at each wave using a 5-item Short Portable Mental Status Questionnaire. Growth models were used to estimate the associations between age, race, baseline status, and longitudinal changes in mental status, controlling for sociodemographic (e.g., education, income) and other health risk factors (diabetes, stroke, tobacco use, depression). Results: Racial disparities were seen beginning in midlife and this relationship was curvilinear. Specifically, blacks had a steeper rate of mental status decline than whites and these disparities persisted after accounting for social and health risk factors ( b = 0.0090, p < 0.0001). Discussion: Study findings demonstrate disparities emerge at middles ages and worsen as age increases. This finding highlights the importance of addressing racial disparities in cognition across a larger part of the adult life course. By doing so, we may better be able to capture early-life exposures that influence later-life cognitive outcomes and ultimately lead to disparities.